The Integration of Belom Bahadat Values in Christian Religious Education as an Effort to Strengthen the Christian Character of Students - Ananda Ananda; Rinto Hasiholan Hutapea; Merry Bendelina Asalaka (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2026)
This study aims to analyze the integration of Belom Bahadat values in Christian Religious Education as an effort to strengthen the Christian character of grade XI students of Textile Crafts at SMKN 4 Palangka Raya. The research uses a qualitative approach with a descriptive method. The results of the study show that the integration of Belom Bahadat values is realized through the learning of Christian Religious Education which emphasizes example, coaching, mentoring, service, social interaction, and daily relationships between teachers and students. The values of Belom Bahadat, such as civilized living, mutual respect, responsibility, maintaining harmony, and caring for others, are internalized in line with Christian values so that they are able to strengthen the character of students in spiritual, moral, and social aspects. This study emphasizes that the integration of local wisdom of Belom Bahadat in Christian Religious Education is an effective contextual approach in shaping students' Christian character and strengthening the relevance of local culture-based character education in the school environment.